Pathologic Findings of Cranial Abscesses Involving the Pituitary Gland in Free-Ranging White-Tailed Deer (Odocoileus virginianus) in Pennsylvania - Jack Timmons; Matthew Shaub; Luke Scherer; Ian Gereg; Lauren Maxwell; Lane Potts; Madison Stevens; Madeline Vile; Erica A. Miller; Kevin D. Niedringhaus (Animals)
Intracranial abscesses are a common cause of morbidity and mortality in neurologic free-ranging white-tailed deer (Odocoileus virginianus). These infections are typically attributed to Trueperella pyogenes and occur most often in adult males with concurrent antler and skull infections. A subset of intracranial abscesses in white-tailed deer are localized to the pituitary gland, with previously described reports in five white-tailed deer. In this case series, five additional free-ranging white-tailed deer in Pennsylvania were diagnosed with pituitary abscesses at necropsy. Two cases were female deer, and four cases were yearling or juvenile deer. Two cases presented with conjunctivitis and keratitis due to extension of pituitary abscesses into the retrobulbar and peri-orbital spaces. One case had a concurrent liver abscess. This case series demonstrates a unique clinical presentation of keratitis and conjunctivitis and emphasizes the potentially unique pathogenesis for pituitary abscesses compared to other intracranial abscesses described in white-tailed deer.